2009
DOI: 10.1074/jbc.m808850200
|View full text |Cite
|
Sign up to set email alerts
|

The Myosin-binding Protein C Motif Binds to F-actin in a Phosphorylation-sensitive Manner

Abstract: Cardiac myosin-binding protein C (cMyBP-C) is a regulatory protein expressed in cardiac sarcomeres that is known to interact with myosin, titin, and actin. cMyBP-C modulates actomyosin interactions in a phosphorylation-dependent way, but it is unclear whether interactions with myosin, titin, or actin are required for these effects. Here we show using cosedimentation binding assays, that the 4 N-terminal domains of murine cMyBP-C (i.e. C0-C1-m-C2) bind to F-actin with a dissociation constant (K d ) of ϳ10 M and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

45
340
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(393 citation statements)
references
References 46 publications
45
340
4
Order By: Relevance
“…The cMyBP-C domains primarily involved in binding actin appear to be the C1 and M-domains (9,15,16,20), although there is evidence that C0 may be important (10,14). Previous modeling suggested that the C0 and C1 domains could clash with Tm in its blocked position (25,27,28), whereas experiments in which expressed N-terminal fragments were added to skinned cardiac myocytes implicated the ProAla-rich domain between C0 and C1 in modulating Ca 2+ activation of crossbridge cycling (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cMyBP-C domains primarily involved in binding actin appear to be the C1 and M-domains (9,15,16,20), although there is evidence that C0 may be important (10,14). Previous modeling suggested that the C0 and C1 domains could clash with Tm in its blocked position (25,27,28), whereas experiments in which expressed N-terminal fragments were added to skinned cardiac myocytes implicated the ProAla-rich domain between C0 and C1 in modulating Ca 2+ activation of crossbridge cycling (46).…”
Section: Discussionmentioning
confidence: 99%
“…We note, finally, that cMyBP-C phosphorylation in response to beta-adrenergic stimulation leads to enhanced cardiac contractility (53). Serine phosphorylation in cMyBP-C's M-domain by a host of kinases reduces the affinity of the N terminus for actin (15) and myosin (7). Therefore, modulation of cMyBP-C's binding capacity by phosphorylation may add a measure of tunability to cMyBP-C's regulation of cardiac contractility in response to physiological stress.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of results indicate that the N-terminal domains of cMyBP-C influence force activation through a direct interaction with actin. 71,[73][74][75] Data from small-angle solution scattering have provided new insights into the structure of cMyBP-C and its interactions with actin and how they might modulate the primary Ca 21 -signal.…”
Section: Cardiac Myosin Binding Protein Cmentioning
confidence: 99%
“…β-Adrenergic-stimulated phosphorylation of these serines is believed to enhance cardiac contractility (11,12), and a high level of phosphorylation appears to be critical to normal cardiac function, whereas dephosphorylation has been associated with heart failure (13)(14)(15). Although the mechanistic role of cMyBP-C phosphorylation in vivo remains unclear, it is known to reduce the extensibility of the M-domain (10,16), diminish the binding of cMyBP-C to actin (17,18) and to myosin S2 (19), and to tune cMyBP-C's ability to modulate actomyosin activity in vitro (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%